Buckyballs In The Treatment of Alzheimer’s Disease - Yaramala, Akhila; Samanthapudi, Bhavana (Asian Journal of Pharmaceutical Research and Development, 2020)
Buckyball is the first nanoparticle discovered in the year 1985 by the trio scientists Richard Smalley, Harry Kroto, and Robert Curl. Buckyballs also called as fullerene. Fullerene is a powerful antioxidant that reacts with free radicals that cause cell death. Fullerenes and their derivatives have the Antiviral activity to treat the HIV infection. Two of the several brain changes that occur in Alzheimer’s disease are β-amyloid plaques and tau tangles present outside and inside the neurons respectively. The changes in brain, cerebrospinal fluid and blood indicate the earliest sign of Alzheimer's disease (biomarkers) even in the absence of memory loss. Ukrainian scientists discovered Carbon 60 or C-60 or Fullerene or Buckyballs. Through the microinjection C60HyFn (0.46nmol/µl) is injected into the hippocampus. It reduces the deposition of β-amyloid in the pyramidal neurons of hippocampal CA 1 neuron.